CROSSWORD GAME MEDIA TO IMPROVE LANGUAGE ASPECTS IN EARLY CHILDHOOD - Sarilah, Sarilah; Mokodenseho, Sabil; Subroto, Desty Endrawati; Nugroho, Wahyu; Apriyansyah, Dede (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2023)
This study aimed to determine the effectiveness of crossword game media in improving language aspects in children aged 5-6 years. This research uses Research and Development (R&D) research methodology. The primary data source in this study were 33 children aged 5-6 years at Nahdlatul Wathan Kindergarten in West Nusa Tenggara. The results of this study show that crossword game media effectively improves the language aspects of children aged 5-6 years. This is evident from using the crossword game media 11 children obtained the undeveloped category, six children in the Begin to Develop category, while no children obtained the Developing As Expected and Developing Very Well categories. After using the crossword game media, eight children obtained the category Starting to Develop, six children in the Developing As an Expected category, and two children in the Very Good Developing category, while no more children obtained the Undeveloped category.